Evaluation of Post-Vaccination Immunity in Children and Adolescents after Viral Hepatitis B Vaccine - Anna A. Khamidulina; Irina L. Solovеva; Mikhail P. Kostinov; Valentina B. Polishchuk; Natalia V. Firsova; Atabeg B. Achilov; Tatiana N. Nikitina; Darya A. Isayeva; Darya D. Petrunina; Ksenia M. Korotkova; Yekaterina А. Gerlinger; Naida A. Magomedova (Педиатрическая фармакология, 2024)
Vaccination against viral hepatitis B is an effective method of protection against this infection. There is multiple decrease in the hepatitis B incidence. However, there was increase in chronic hepatitis B by 42.5%, 15 cases of acute viral hepatitis B in children and 2 deaths from this infection were registered according to the state report “On the sanitary and epidemiological wellbeing of the population of the Russian Federation for 2022”. The criteria for evaluating protection against viral hepatitis B are the anti-HBs level and the duration of post-vaccination immunity.Objective. The aim of the study is to evaluate the duration of postvaccination immunity in temporal aspect in children and adolescents vaccinated against viral hepatitis B.Methods. Prospective open-label study was conducted to assess post-vaccination immunity against viral hepatitis B in 143 children and adolescents. The study of anti-HBs was implemented via the immunoenzyme test system “Vectohep B-HBs-antigen”. Microsoft Office Excel 2010 package and the Prism9 program (GraphPad, USA) were used for statistical analysis.Results. It has been shown that hepatitis B vaccine provides 100% seroconversion. However, decrease in anti-HBs levels was revealed already 6 months after vaccination in 15.07% of cases of seronegative individuals, after 1 year their number has increased up to 28.77% of cases. On average, every fourth person had low protective level of anti-HBs. Almost two-thirds of adolescents became seronegative by the age of 14.Conclusion. Vaccination against viral hepatitis B ensures the maximum production of anti-HBs 1 month after the completed vaccination in 100% of cases. Antibody level begins to decrease 6 months after the third completed vaccination against hepatitis B, and in 14 years, 72.74% of those immunized become seronegative. All of these dictates the need to consider a booster dose in adolescents at the age of 14 years.